2010
DOI: 10.1007/s11738-010-0656-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of salt stress on physiological and antioxidative responses in two species of Salicornia (S. persica and S. europaea)

Abstract: The effects of salt stress on growth parameters, free proline content, ion accumulation, lipid peroxidation, and several antioxidative enzymes activities were investigated in S. persica and S. europaea. The seedlings were grown for 2 months in half-strength Hoagland solution and treated with different concentrations of NaCl (0, 85, 170, 340, and 510 mM) for 21 days. The fresh and dry weights of both species increased significantly at 85 and 170 mM NaCl and decreased at higher concentrations. Salinity increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
37
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 49 publications
12
37
1
1
Order By: Relevance
“…Superoxide dismutase plays a key role in cellular defense mechanisms against ROS. Its activity modulates the relative amounts of O2 -and H2O2, and decreases the risk of OH• radical formation, which is highly reactive and may cause severe damage to membranes, protein and DNA (Aghaleh et al, 2011). In this work, salt stress significantly (P < 0.05) increased SOD activity in root of both cultivars (Figure 4), which could be a build-up of a protective mechanism to reduce oxidative damage triggered by salt stress (Sairam et al, 2005;Wang and Han, 2009).…”
Section: Resultssupporting
confidence: 49%
“…Superoxide dismutase plays a key role in cellular defense mechanisms against ROS. Its activity modulates the relative amounts of O2 -and H2O2, and decreases the risk of OH• radical formation, which is highly reactive and may cause severe damage to membranes, protein and DNA (Aghaleh et al, 2011). In this work, salt stress significantly (P < 0.05) increased SOD activity in root of both cultivars (Figure 4), which could be a build-up of a protective mechanism to reduce oxidative damage triggered by salt stress (Sairam et al, 2005;Wang and Han, 2009).…”
Section: Resultssupporting
confidence: 49%
“…It may be concluded that all the three halophytes were similar in their sensitivity to salinity. At high salinity, growth reduction might either be caused by a reduced ability to adjust osmotic potential, consequently this results in saturation of solute uptake system, or because of excessive demand for energy requirements of such systems (Aghaleh et al 2011). Furthermore, increased soluble protein content was observed maximum in Z. simplex and lowest in T. triquetra callus cultures at lower salinity stress.…”
Section: Discussionmentioning
confidence: 97%
“…Plants have evolved adaptive mechanisms which can be understood and exploited as an important resource for development of crops tolerant to extremities (Lokhande & Suprasanna 2012). Halophytic species that live under conditions of high salinity exhibit succulence by altering their energy metabolism (Aghaleh et al 2011) and salinity tolerance in the form of osmotic adjustment (Flowers & Colmer 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These defense mechanisms include antioxidant systems (Li et al, 2009;Aghaleh et al, 2010) and osmotic adjustment (by increasing of compatible metabolites) (Hongbo et al, 2006). Plant antioxidants contain enzymatic and non-enzymatic systems.…”
Section: Methodsmentioning
confidence: 99%